Metabolite profiling, production of terpenoid and 11αOH-KA, and free radical scavenging capacity of Adenostemma lavenia under different light intensities and nitrogen dosage - Anisya Elsa Shafira, Rifan Nurfalah, Sandra Arifin Aziz, Muhammad Farid, Taopik Ridwan, Hiroshi Takemori, Mohamad Rafi, Irmanida Batubara (Journal of Applied Pharmaceutical Science, 2024)
Adenostemma lavenia (Asteraceae) is a medicinal plant reported to contain high levels of flavonoids, alkaloids, terpenoids, and potential as a free radical scavenging. This study aims to determine the profile of metabolite, optimum production of terpenoids, and ent-11α-hydroxy-15-oxo-kaur-16-en-19-oic acid (11αOH-KA), and also evaluate the free radical scavenging capacity of A. lavenia cultivated under different shading and doses of nitrogen. The experimental design used was nested. Metabolite production was obtained from the total metabolite and the dry weight of the harvest. Total terpenoids were analyzed using an ultraviolet-Vis spectrophotometer and 11αOH-KA was analyzed using high-performance liquid chromatography. Determination of free radical scavenging capacity was carried out by the 2,2-diphenyl-1-picrylhydrazyl method and metabolite profiling using liquid chromatography-mass spectrometry (LC-MS/MS). The optimum terpenoids and 11αOH-KA production were obtained under 25% shade or nitrogen 45 kg/ha. A 25%, while free radical scavenging capacity tended to increase at 50% shade or N 90 kg/ha. The LC-MS/MS results showed the metabolite profile of A. lavenia. These metabolites were categorized as terpenoids, flavonoids, alkaloids, amino acids, and fatty acids groups confirmed in A. lavenia leaf extract cultivated under different shading and doses of N. The most identified compounds were the terpenoid group.
Keywords: Adenostemma lavenia, DPPH, metabolite productions, nested design